Application of Virtual Reality Technology in Vehicle Ergonomics and Human-Computer Interaction - Sun, Wenyu (International Scientific Technical and Economic Research, 2025)
With the development of intelligence and personalization in the automotive industry, the application of virtual reality (VR) technology in vehicle ergonomics and human-computer interaction design has become an important research field. This paper explores how virtual reality technology can play a role in vehicle seat design, cockpit layout, human-computer interaction interface and safety assessment. Through VR technology, designers can simulate and optimize different design schemes in a virtual environment, thereby improving the efficiency and accuracy of the design and reducing discomfort and potential safety hazards. In addition, virtual reality also provides a more intuitive and convenient way for drivers to interact with the on-board system, further improving the driving experience and the level of vehicle intelligence. Although virtual reality technology still faces challenges in terms of equipment cost and comfort, with the development of hardware technology and the integration of cross-domain technologies, VR has broad application prospects in automotive design. In the future, virtual reality technology will play a greater role in improving driving safety, comfort and intelligence, and promote innovation and development in the automotive industry.